1985
DOI: 10.1111/j.1365-2494.1985.tb01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of faecal indices for predicting phosphorus status of cattle

Abstract: An experiment examining the relationships between dietary and faecal phosphorus (P) concentration and intake and faecal output of P by steers is described. Six forages with a wide range of chemical properties were fed to six steers in a Latin square design. Dietary P concentration was highly associated with faecal P concentration in simple linear regression equations including (r2= 0.91) and excluding (r2= 0.94) animal variation. The regression slopes were similar to those in an Australian study involving dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
9
0
6
Order By: Relevance
“…Researchers have used faecal nutrient concentration studies in a variety of indigenous types of wildlife as well as for domestic livestock (Erasmus et al 1978;Belonje & Van den Berg 1980;Holechek et al 1982Holechek et al , 1985Leslie & Starkey 1985;Leite & Stuth 1990;Irwin et al 1993;Grant et al 1995Grant et al , 1996Grant et al , 2000MacLeod et al 1996;Vorster 1996;Wrench et al 1996Wrench et al , 1997Van der Waal et al 2003;Codron et al 2005;Botha & Stock 2005;Mbatha & Ward 2006). Leslie & Starkey (1985) found that faecal nitrogen concentration increases with an increase of the nitrogen concentration of the herbivore's diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have used faecal nutrient concentration studies in a variety of indigenous types of wildlife as well as for domestic livestock (Erasmus et al 1978;Belonje & Van den Berg 1980;Holechek et al 1982Holechek et al , 1985Leslie & Starkey 1985;Leite & Stuth 1990;Irwin et al 1993;Grant et al 1995Grant et al , 1996Grant et al , 2000MacLeod et al 1996;Vorster 1996;Wrench et al 1996Wrench et al , 1997Van der Waal et al 2003;Codron et al 2005;Botha & Stock 2005;Mbatha & Ward 2006). Leslie & Starkey (1985) found that faecal nitrogen concentration increases with an increase of the nitrogen concentration of the herbivore's diet.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that faecal nitrogen and phosphorus concentrations can be used as indicators of the nutritive intake of a herbivore (Belonje 1978;Belonje & Van den Berg 1980;Holechek et al 1985;Grant et al 1996;Wrench et al 1997;Botha & Stock 2005) and that comparing the faecal components of animals in different habitats could be of assistance in understanding their nutritional ecology (Erasmus et al 1978;Wofford et al 1985;Wrench et al 1997; Van der Waal et al 2003). Researchers have used faecal nutrient concentration studies in a variety of indigenous types of wildlife as well as for domestic livestock (Erasmus et al 1978;Belonje & Van den Berg 1980;Holechek et al 1982Holechek et al , 1985Leslie & Starkey 1985;Leite & Stuth 1990;Irwin et al 1993;Grant et al 1995Grant et al , 1996Grant et al , 2000MacLeod et al 1996;Vorster 1996;Wrench et al 1996Wrench et al , 1997Van der Waal et al 2003;Codron et al 2005;Botha & Stock 2005;Mbatha & Ward 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Analisando as concentrações de P nas fezes, Tabela 8 -Regressão linear relacionando concentrações fecais de P (%P) na matéria seca (YMS) ou na matéria orgânica (YMO), obtidas de amostras retais, à quantidade do elemento na dieta (g/dia, X) nota-se que as equações de regressão encontradas (Tabela 7) foram muito semelhantes àquelas descritas por HOLECHECK et al (1985) e MOIR (1960, para a estimativa da concentração de P na dieta, a partir da concentração de P na matéria seca orgânica fecal. Aparentemente, o fato de serem utilizadas amostras de fezes coletadas diretamente do reto não alterou a equação obtida com a coleta total de fezes.…”
Section: Nicodemo Et Alunclassified
“…A large amount of research has attempted to measure P responses and have come to the conclusion that faecal P alone is not a sufficient indicator of when a response to fertilisation or supplementation of breeding cattle will occur (Winks et al, 1977;Holechek et al, 1985;Read et al, 1986c;Wadsworth et al, 1990;Ternouth and Coates, 1997;Karn, 2001;Dixon and Coates, 2010;Jackson et al, 2012). The suggestion of FP:ME being a good indicator of dietary P status is based on research conducted at Springmount and Lansdown in north Queensland.…”
Section: The Fp:me Ratiomentioning
confidence: 99%
“…However, there is little standardisation and the method is invasive and not practical for commercial measurement (Quigley et al, 2015). A large amount of research has also concluded that measurement of faecal P alone is not an accurate indicator of whether a response to fertilisation or P supplementation of breeding cattle will result in a significant improvement in performance (Winks et al, 1977;Holechek et al, 1985;Read et al, 1986c;Wadsworth et al, 1990;Ternouth and Coates, 1997;Karn, 2001;Dixon and Coates, 2010;Jackson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%